1991
DOI: 10.1128/aem.57.10.2986-2994.1991
|View full text |Cite
|
Sign up to set email alerts
|

Factors Limiting Aliphatic Chlorocarbon Degradation by Nitrosomonas europaea : Cometabolic Inactivation of Ammonia Monooxygenase and Substrate Specificity

Abstract: effect on the cells; and (iii) compounds which were cooxidized and produced a turnover-dependent inactivation of ammonia oxidation by N. eluropaea. MATERIALS AND METHODS Growth and preparation of cells. Cells of N. europaea ATCC 19718 were grown in batch cultures (1 to 2 liters) and harvested by centrifugation as described previously (15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 23 publications
3
108
1
1
Order By: Relevance
“…It is well known that enzymatic transformation of certain compounds can result in deleterious metabolic effects.2.1S, 18,28,34,42 However, the distinct mechanisms of inhibition and inactivation have not been modeled entirely satisfactorily to date. Competition for the primary enzyme of interest has been noted p r e v i o u~l y ,~~ and models have been proposed in which enzyme inactivation is expressed in terms of decreases in "active biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that enzymatic transformation of certain compounds can result in deleterious metabolic effects.2.1S, 18,28,34,42 However, the distinct mechanisms of inhibition and inactivation have not been modeled entirely satisfactorily to date. Competition for the primary enzyme of interest has been noted p r e v i o u~l y ,~~ and models have been proposed in which enzyme inactivation is expressed in terms of decreases in "active biomass.…”
Section: Discussionmentioning
confidence: 99%
“…( 2 ) oxidation of the nongrowth substrate consumes reductant that must be replaced e n d o g e n~u s l y "~~~; and (3) oxidation of the nongrowth substrate can yield products toxic to the monooxygenase enzyme and other proteins. 16,34 However, evidence suggests that cells may be able to counter these inhibiting and inactivating effects under some circumstances. Bacteria are known to synthesize particular proteins in response to heat shock and other s t r e s~e s .~'~~ In addition, it has been shown that ammonia-oxidizing bacteria can recover from TCE toxicity, in the absence of TCE, by de novo enzyme synthesis.18934 Recovery potential in the presence of TCE has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many other organic contaminants, including many herbicides, have no effect on nitrification [14]. Rasche et al [15] demonstrated that ammonia oxidation to nitrite by Nitrosomonas europea in pure culture is inhibited by several chlorinated solvents due to an interaction with the ammonia monooxygenase enzyme (AMO). It was found that if sufficient time was allowed to elapse for de novo protein synthesis, nitrification activity could be reestablished.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of aniline, one of the most important amines produced, is thought to be caused by competition with ammonia for the active site of the enzyme AMO. A key enzyme, AMO is known to be inhibited by a variety of chemicals such as aromatic compounds, aliphatic chlorocarbon, ethylene, chloroethane, and 1-1-1 trichloroethane (Hyman and Wood, 1984;Arp, 1993, 1994;Rasche et al, 1990Rasche et al, , 1991.…”
Section: Model Developmentmentioning
confidence: 99%